การจัดการขยะมูลฝอย เพื่อลดปัญหาภาวะโลกร้อน - ด้วงชนะ วีระยุทธ (Suan Sunandha Asian Social Science, 2022)
A change of global weather at present has drawn not much attention from people. More importantly, there are many people who still lack understanding that everyone is a apart of the change. The level of participation depends on behavior and lifestyle of each person such as consumption, vehicle using as well as the use of different facilities. If one consumes much or depends highly on comfort facilities, he is considered to cause more "Global Warming". All of the consumption and facilities come from manufacturing process. The manufacturing process can cause toxic gases especially greenhouse effect which mainly causes "Global Warming". The catastrophe which is threatening the world now is carbon dioxide, methane, greenhouse effect gases. Huge amount of gases caused by human has been released to thicken the ozone. It can keep the heat of the sun from penetrating to the ozone which comes from the increment of carbon dioxide that released by human. Methane comes from fuel burnings, transportation, and manufacturing factories. Deforestation can reduce the mechanism to take carbon dioxide out of the ozone and it bounces back to the world as a global warming. Global warming not- only affects countries which release greenhouse gases, it can also affect Thailand. It affects agriculture and water sources in Thailand. There is a tendency that the weather change in Thailand can reduce the water quantity at 5-10% which affects agricultural production, es- pecially rich rice which is the main economic product of the country. Rice farming depends on rains and sunshine as well as soil moisture and suitable temperature. Garbage is one of the main problems of the community. If a community consists of many people, there are more activities and they can create offices, industries, and agriculture. They are a common sight in communities. If the garbage is not properly managed, it can cause other environmental problems such as water, soil, air, and scenery Pollution and global warming. To decide which way or process to be used to treat it depends on the weather, geography, technology, and economy of each community. Garbage management in a hygienic way is to bury in order to reduce methane.which comes from the decay of the g·arbage. Methane is a greenhouse gas which causes change in the worldweather or global warming. Energy production from biogas, from garbage pit, is the return of the methane. It is an option which can reduce the global warming. Burying is a good way to eradicate garbage because it can reduce the global warming and it can create the biogas, especially methane which isa flammable greenhouse gas. With this quality of being flammable, if there is an efficient way of garbage management, methane can be collected to a big amount. Not only it can provide heat, it can also reduce the release of gases which is the cause of the global warming. Biogas from the garbage pit comes from the biochemical reaction of the garbage. It can produce methane, carbon dioxide, ammonia, carbon monoxide, hydrogen sulfide, and nitrogen. All of them are greenhouse gases which are the cause of global warming. There is more methane and carbon dioxide than other gases. If the condense of methane is more than 50%, it can be used to produce energy. Therefore, the alleviation of global warming is something that everyone has to realize and cooperate to change behavior in daily life to help reduce greenhouse gas. The main government unit, which is important and the closest to people is a local administration organization. It has to give advice and encourage people to participate in garbage management of each community so as to reduce the global warming. Human causes problems, so human should solve them. Global warming is caused by human, therefore human should find solution and prevention before it is too late. much more consumption. As a result, there are more leftovers from conducting those activities such as garbage from houses,